The Novel Coronavirus and Undocumented Farmworkers in the United States. (May 2021) - Matthew, Olayemi O.; Monaghan, Paul F.; Luque, John S.
The Covid-19 pandemic has greatly impacted frontline workers' health in 2020. The objective of this commentary is to evaluate some of the challenges faced by undocumented farmworkers in the context of the current global pandemic and possible risk mitigation strategies. Undocumented farmworkers make considerable contributions to the U.S. economy and food production, but they are at an elevated risk for contracting Covid-19. Their risk is compounded by their employment and legal status, as well as their poor working and living conditions which makes it difficult for them to observe Covid-19 precautionary measures. U.S. immigration policy disincentivizes undocumented farmworkers from seeking healthcare services. Contact tracing challenges could be overcome by gaining trust with subsequent increased testing and care. Extending eligibility of safety net programs for undocumented farmworkers will help to ease the burden of Covid-19, thereby improving their overall health and productivity.